Assesment of robust tree detection technique for inter row trees tracking UAV based on simultaneous localization method / Norashikin M. Thamrin and Nor Hashim Mohd. Arshad - M. Thamrin, Norashikin; Mohd. Arshad, Nor Hashim (2014)
ln previous work, there had been extensive research on row tracking by academicians. Most of row tracking techniques were implemented on mobile robot and the method varies in terms of sensors and algorithm used for detection for example Global Positioning System (GPS), vision based, laser, mechanical sensors and sensor fusion. Inter-row tracking technique of a mobile robot can be upgraded to Unmanned Aerial Vehicle (UAV). UAV has not been specifically designed to function on row tracking but has been used as platform for tree detection from aerial platform view, however such technique, inherit problems in identifying individual trees from different row with narrow inter-row spaces or recognizing row that is completely covered by multi-layered tree crowns.